Rational design of carbon nitride photoelectrodes with high activity toward organic oxidations - Pulignani,C; Mesa,C; Hillman,S; Uekert,T; Gimenez,S; Durrant,J; Reisner,E (Angewandte Chemie International Edition, 2022)
Carbon nitride (CNx) is a scalable polymeric light-absorber with excellent performance in photocatalytic suspension systems, but the activity of CNx photoelectrodes has remained low. Here, cyanamide-functionalized CNx (NCNCNx) has been co-deposited with ITO nanoparticles on a 1.8 Å thick alumina-coated FTO-glass electrode. Transient spectroscopy and impedance measurements support that ITO acts as conductive binder and improves the electron extraction from the NCNCNx, whilst the alumina underlayer reduces the electrical resistance between the ITO and the FTO-coated electrode. The Al2O3|ITO:NCNCNx electrode displays a new benchmark performance for CNx-based photoanodes with a remarkably low onset of –0.4 V vs the reversible hydrogen electrode (RHE) and an outstanding 1.4 ± 0.2 mA cm–2 at 1.23 V vs RHE for the selective oxidation of 4-methylbenzyl alcohol to the corresponding aldehyde. This facile assembly will enable the exploration of CNx in fundamental and applied PEC studies, paving the way for the development of high-performance photoelectrodes using other semiconductor powders